(untitled) (Comprehensive Journal of Science, 2026)
Women’s participation from an intersectional feminist perspective: Research on the topic of women’s participation in general, and from an intersectional feminist perspective—where feminist identity intersects with multiple identities such as gender, sex, and race—is a subject that requires our research and investigation. Here, we have attempted to present feminism in its general sense and intersectional feminism in its specific form through feminist representations and their role in the erasure of identity in the past and present, because it is essential to identify the structural flaws that prevent women’s participation in reality, despite the existence of laws and international conventions that seek to advance women’s role in society and prevent their marginalization, as they represent untapped potential and constitute half of society.